2013
DOI: 10.3390/s130303975
|View full text |Cite
|
Sign up to set email alerts
|

Piper nigrum, Piper betle and Gnetum gnemon- Natural Food Sourcewith Anti-Quorum Sensing Properties

Abstract: Various parts of Piper nigrum, Piper betle and Gnetum gnemon are used as food sources by Malaysians. The purpose of this study is to examine the anti-quorum sensing (anti-QS) properties of P. nigrum, P. betle and G. gnemon extracts. The hexane, chloroform and methanol extracts of these plants were assessed in bioassays involving Pseudomonas aeruginosa PA01, Escherichia coli [pSB401], E. coli [pSB1075] and Chromobacterium violaceum CV026. It was found that the extracts of these three plants have anti-QS ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 42 publications
(34 reference statements)
3
32
0
1
Order By: Relevance
“…Additionally, the extracts used in the study did not have any antibacterial activity against all test strains. The present data is supported well with the findings of Tan et al (2013) who reported the anti-QS activity of methanolic extracts of Pip. nigrum against Chr.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the extracts used in the study did not have any antibacterial activity against all test strains. The present data is supported well with the findings of Tan et al (2013) who reported the anti-QS activity of methanolic extracts of Pip. nigrum against Chr.…”
Section: Discussionsupporting
confidence: 93%
“…On account of the importance of such quorum-sensing-inhibitor (QSI) compounds, many studies have recently shown that AHLmediated mechanism could be considered as a promising target on achieving some novel pathways for paralyzing the QS such as Eugenol isolated from clove 7,11,29 . It has been found that the extract from Melicope lunu-ankenda inhibited QS-controlled virulence factors of the human pathogen, P. aeruginosa PAO1 22 . The ethanolic extract isolated from Scutellaria baicalensis Georgi was confirmed to be able to suppress the QS-dependent virulence determinant in Pectobacterium 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to D. pulchra, various higher plants including Medicago truncatula seedlings 9 , garlic, clove 24 , Tremella fuciformis, water lily (Nymphaea sp. ), and pepper extracts 22 were also shown to secrete AHL signal mimic substances and were found to possess anti-QS activity. The finding of QS inhibitor compounds in plants raises the possibility that interfering bacterial quorum sensing using AHL mimic compounds might be of considerable medical and agricultural interest in controlling of bacterial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Adonizio et al [13] highlighted antiquorum sensing (AQS) compounds that may be very promising in the treatment of chronic infections caused by biofilm forming microorganisms. AQS properties of natural compounds are well documented in the literature [13][14][15][16][17]. AQS treatment may be a reliable way to reduce bacterial virulence and attenuate the acquisition of drug resistance by pathogenic bacteria [12].…”
mentioning
confidence: 99%